2012
DOI: 10.1007/s12524-012-0230-7
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of TerraSAR-X Data for Land use/Land Cover Analysis Using Object-Oriented Classification Approach in the African Sahel Area, Sudan

Abstract: Recently, object-oriented classification techniques based on image segmentation approaches are being studied using high-resolution satellite images to extract various thematic information. In this study different types of land use/land cover (LULC) types were analysed by employing object-oriented classification approach to dual TerraSAR-X images (HH and HV polarisation) at African Sahel. For that purpose, multi-resolution segmentation (MRS) of the Definiens software was used for creating the image objects. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The significant impacts of soil salinity on the soil-water-plant system can reduce the nutrient absorption and lead to a considerable decrease of crop productivity [2,3]. Remote sensing has been shown to be a particularly valuable tool for monitoring soil conditions frequently and spatially [4][5][6]. The presence of salts can be detected directly on bare soils with salt crust via the variation of spectral reflectance, and the spectral behaviour of salt has been studied in detail [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The significant impacts of soil salinity on the soil-water-plant system can reduce the nutrient absorption and lead to a considerable decrease of crop productivity [2,3]. Remote sensing has been shown to be a particularly valuable tool for monitoring soil conditions frequently and spatially [4][5][6]. The presence of salts can be detected directly on bare soils with salt crust via the variation of spectral reflectance, and the spectral behaviour of salt has been studied in detail [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] In processing high-resolution remote sensing images, numerous classification algorithms, such as the object-oriented approach, [8][9][10] based on the classification of a support vector machine (SVM) [11][12][13] and Markov random fields (MRF) [14][15][16][17][18] are being developed. Local features [19][20][21][22][23] have been successfully applied to image retrieval, semantic segmentation, and scene understanding.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this difficulty, researchers started utilizing polarimetric SAR (PolSAR) data to study landuse/landcover information (Du & Lee, 1996;Freitas et al, 2008;Pierce, Ulaby, Sarabandi, & Dobson, 1994). The results showed that PolSAR measurements achieved much better classification results than single polarization SAR (Biro, Pradhan, Sulieman, & Buchroithner, 2013;Qi, Yeh, Li, & Zhang, 2015;. PolSAR data were mainly used for mapping landuse/landcover in river catchments (Ahmed, Garg, Singh, & Raman, 2014) and flood affected areas (Manavalan, Rao, Krishna Mohan, Venkataraman, & Chattopadhyay, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Several methods were implemented to identify urban landuse/landcover classes. Some of these methods are supervised classification from backscatter and coherence (Parihar, Das, Rathore, Nathawat, & Mohan, 2014), unsupervised classification (Ince, 2010), object-oriented image analysis, change vector analysis, post-classification comparison (Biro et al, 2013;Qi et al, 2015), change detection matrix (Lê, Atto, Trouvé, Solikhin, & Pinel, 2015), polarimetric decomposition, Pol-SAR interferometry, and decision tree algorithms (Qi, Yeh, Li, & Lin, 2012). Fusion of optical and SAR images also proved to be a useful method in urban landuse/landcover classification.…”
Section: Introductionmentioning
confidence: 99%